Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1155/2019/3961201
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Levels of Knowledge, Attitude, and Practice Associated with Sickle Cell Disease and Premarital Genetic Counseling in 350 Saudi Adults

Abstract: Our study aims to observe the levels of knowledge, attitude, and practice (KAP) associated with sickle cell disease (SCD) and premarital genetic counseling (PMGC) in 351 Saudi adults. The relationships between KAP levels and sociodemographic characteristics (age, gender, marital status, and educational level) were observed. The study was conducted in King Khalid University Hospital between February 21, 2017, and March 7, 2018. A total of 351 Saudi participants attending the primary care clinic were selected us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 24 publications
2
18
1
Order By: Relevance
“…The study had some limitations. First, the sample size was small compared to previous studies,2017 but this was also a reflection of the generally low participation in research among the elderly population in this region,2017 and in the hospital 2018. Second, the findings are less likely to be a representative of the adult population in Riyadh city in Saudi Arabia, as many older adults who have multiple medical issues may be attending any of the other public or private eye clinics and hence might not be attending the ophthalmology clinic of this hospital.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The study had some limitations. First, the sample size was small compared to previous studies,2017 but this was also a reflection of the generally low participation in research among the elderly population in this region,2017 and in the hospital 2018. Second, the findings are less likely to be a representative of the adult population in Riyadh city in Saudi Arabia, as many older adults who have multiple medical issues may be attending any of the other public or private eye clinics and hence might not be attending the ophthalmology clinic of this hospital.…”
Section: Discussionmentioning
confidence: 84%
“…First, the sample size was small compared to previous studies, 15,20,21 but this was also a reflection of the generally low participation in research among the elderly population in this region, 20,21 and in the hospital. 37,38 Second, the findings are less likely to be a representative of the adult population in Riyadh city in Saudi Arabia, as many older adults who have multiple medical issues may be attending any of the other public or private eye clinics and hence might not be attending the ophthalmology clinic of this hospital. Despite these limitations, the study provided recent evidence confirming the burden of visual impairment in Riyadh city and reiterates the need for more regular and obligatory ophthalmology assessment for Saudi adults, either during visits to optical stores or public hospitals, where visual checks are often conducted in the Kingdom.…”
Section: Strengths and Limitationsmentioning
confidence: 96%
“…We expressed the descriptive statistics such as participant characteristics in frequencies and presented in tables. We graded the level of knowledge depending on the number of correct responses scored from the questionnaires which was constructed from different literature which assessed the level of knowledge on SCD in different groups including pregnant women, also modified to fit the local context ( Babalola et al, 2019 ; Obed et al, 2017a ; Al-Qattan et al, 2019 ). A correct answer was scored as “1” while a wrong response was scored as “0”.…”
Section: Methodsmentioning
confidence: 99%
“…However, in our study, there were four predictors for marriage cancellation, as described above. With regard to PMS knowledge and enrollment in a health-related college, a study conducted in Saudi Arabia also showed a significant correlation between PMS knowledge and attitude [ 42 ]. This underlines the importance of increasing PMS knowledge, particularly for future couples to help them make informed decisions.…”
Section: Discussionmentioning
confidence: 99%